O imaginário político da nova república nos acordes do rock nacional (1982-1992) - Rodrigo César Ribeiro Horta (2020)
The primary objective of this research work is to situate the National Rock within the modern brazilian popular music tradition and to look into the political imaginary brought about the genre between the years of 1982 and 1992. As such, in the first part, the imaginary surrounding the genre in the country and the relationship between the arising National Rock bands and the preceding musical styles is analyzed. In the second part, the political imaginary elaborated by such bands on the military, the state and the nation, throughout the brazilian democratic transition is also examined.